A green protocol for ligand, copper and base free Sonogashira cross-coupling reaction. Issue 33 (17th August 2016) - Dewan, Anindita; Sarmah, Manashi; Bora, Utpal; Thakur, Ashim J.
Graphical abstract: Highlights: All the reactions are carried out in the absence of any organic or inorganic base in aqueous medium. It is a ligand, copper and amine free approach for Sonogashira reaction. Electronically diversified aryl iodides and electronically diversified aryl or alkyne acetylene can be used as substrate. Natural feedstock 'water extract of banana peels ash (WEB)' has been used as a co-solvent. Abstract: A convenient methodology has been developed for palladium catalyzed Sonogashira cross-coupling reaction under mild and green reaction conditions. The reaction is catalyzed by an in situ generated catalytic system based on Pd(OAc)2 and WEB (water extract of banana peels ash) in the absence of any organic or inorganic base, ligand and copper salt with excellent yield of cross coupled product. The reaction condition is compatible with electronically diversified aryl iodides and electronically diversified aryl or aliphatic alkyne. The present method developed for the Sonogashira reaction offers many advantages including high conversion, high economy, the involvement of non-toxic green substrates, etc.